2004
DOI: 10.1186/1472-6920-4-8
|View full text |Cite
|
Sign up to set email alerts
|

Using a formative simulated patient exercise for curriculum evaluation

Abstract: Background: It is not clear that teaching specific history taking, physical examination and patient teaching techniques to medical students results in durable behavioural changes. We used a quasiexperimental design that approximated a randomized double blinded trial to examine whether a Participatory Decision-Making (PDM) educational module taught in a clerkship improves performance on a Simulated Patient Exercise (SPE) in another clerkship, and how this is influenced by the time between training and assessmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…In a study of dietetic interns, Litchfield, Oakland, and Anderson (2002) found greater pretest-posttest improvement in critical thinking and clinical competency among those with online instruction. Solomon, Laird-Fick, Keefe, Thompson, and Noel (2004) found that medical students exposed to a curriculum that included an online demonstration performed better in a single SP encounter than those who did not. Our study adds to this literature by investigating both medical and dental students, using a highly structured SP assessment that included various encounters, using highly reliable and well-validated assessment tools, and investigating the relationship between learner scoring accuracy and performance.…”
Section: Discussionmentioning
confidence: 97%
“…In a study of dietetic interns, Litchfield, Oakland, and Anderson (2002) found greater pretest-posttest improvement in critical thinking and clinical competency among those with online instruction. Solomon, Laird-Fick, Keefe, Thompson, and Noel (2004) found that medical students exposed to a curriculum that included an online demonstration performed better in a single SP encounter than those who did not. Our study adds to this literature by investigating both medical and dental students, using a highly structured SP assessment that included various encounters, using highly reliable and well-validated assessment tools, and investigating the relationship between learner scoring accuracy and performance.…”
Section: Discussionmentioning
confidence: 97%
“…The scoping review included 12 studies which described 11 SDM training courses embedded in undergraduate medical education (see Table 2 ). [ 22 33 ] The studies were conducted in six countries: Australia (n = 1), the Netherlands (n = 1), Canada (n = 1), Switzerland (n = 1), Germany (n = 3), and the United States (n = 5). The study designs included one randomized controlled trial, six quasi-experimental studies, and five observational studies.…”
Section: Resultsmentioning
confidence: 99%
“…Training courses delivered in the third year were usually integrated in clinical clerkship. [ 26 , 27 , 31 , 33 ] Nine SDM courses were integrated into an organ-based[ 24 ] or symptom-based module,[ 24 , 28 , 29 ] or embedded into a specific training program. [ 19 , 22 , 23 , 25 , 26 , 31 , 32 ] Only one SDM training course was standalone.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several approaches have been previously described and have reported success in learners' self-reported understanding of the importance of engaging patients in decision making. [13][14][15][16] Despite these challenges, informed decision making is emphasized in many areas of primary care, including cancer screening. 1,4 For breast cancer screening, most recommendations now call for initiating screening mammography for women beginning at age 40, but encourage clinicians to discuss the benefits and potential harms of screening with their patients and engage them in the decision-making process.…”
Section: Introductionmentioning
confidence: 99%